Christian Context of Historical Novel (Zakhar Prilepin’s “Abode”) - O. Yu. Osmukhina; A. D. Karpov; E. A. Beloglazova (Научный диалог)
The specificity of the synthesis of elements included in the historical narrative, and Christian motives, images in the novel of the largest contemporary Russian prose writer Zakhar Prilepin is comprehended in the article. The relevance of the article is due to the need to build a coherent and consistent history of the development of Russian literature over the past two decades, an important part of which is the legacy of the popular writers. The scientific novelty of the work lies in the fact that for the first time in Russian literary criticism “Abode” is considered from the proposed perspective: its genre specificity is analyzed in a Christian context. It has been established that, despite the presence of elements of documentary, adventurous, love-psychological novels, in terms of genre, “The Abode” can be attributed to a historical novel (it depicts a turning point in Russian history through a conflict between historical figures and fictional “average” heroes, combines historical facts and fiction). At the same time, an interest in eternal moral issues, problems of life and death, conscience and duty, love and fidelity in their Christian understanding becomes a feature of Prilepin’s understanding of the historical theme. In their work, the authors of the article used comparative historical, biographical, socio-cultural methods, as well as the method of a holistic analysis of a work of art.